Adherence to recommendations for cervical and breast cancer screening in systemic sclerosis - Caramaschi, P.; Biasi, D.; Caimmi, C.; Vaccari, R.; Dal Forno, I.; Pieropan, S.; Adami, S. (Reumatismo, 2015)
The aim of the study was to evaluate the adherence of systemic sclerosis (SSc) female patients to cervix and breast cancer screening procedures, as suggested by local guidelines. A cohort of 84 SSc women was asked if they had undergone mammography and Pap test during the previous 2- and 3-year intervals, as indicated according to the Italian recommendations. The results were compared with those collected in patients affected by other chronic rheumatic disorders and in the general population. More than 85% of SSc women declared to comply with an age-related cervix and breast cancer screening schedule. The data were similar to those collected in patients affected by other chronic rheumatic disorders, whereas the subjects belonging to the general population reported to undergo breast cancer screening more frequently. Among SSc women, neither the educational level, nor the lung and skin involvement influenced their cancer screening program compliance. Only a positive history of ischemic digital ulcers seemed to interfere with mammography. Our study reported a very high percentage of SSc female patients who adhered to programs for the early detection of cervical and breast cancer. The significant adherence to guidelines may be due to the schedule adopted by the local health public service, which regularly invites eligible subjects by mail to undergo cancer screening at no charge.